2019
DOI: 10.1177/000313481908500525
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy and Resection Margin Status in Colorectal Liver Metastasis Patients: A Propensity Score–Matched Analysis

Abstract: In this article, we compared the early and long-term outcomes of patients with metastatic colorectal cancer treated with chemotherapy followed by resection with those of patients undergoing surgery first, focusing our analysis on resection margin status. Patients who underwent liver resection with curative intent for colorectal liver metastases from July 2001 to January 2018 were included in the analysis. Propensity score matching was used to reduce treatment allocation bias. The cohort comprised 164 patients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The liver margin is an important factor in determining whether radical treatment can be achieved. Over the years, knowledge of the R0 margin of the liver has gradually narrowed from 1 cm to ≥1 mm (9)(10)(11)(12). Even though the R1 margin of the liver is now recognized as less than 1 mm, there are conflicting reports on whether the R1 margin is an independent risk factor for CRLM.…”
Section: Introductionmentioning
confidence: 99%
“…The liver margin is an important factor in determining whether radical treatment can be achieved. Over the years, knowledge of the R0 margin of the liver has gradually narrowed from 1 cm to ≥1 mm (9)(10)(11)(12). Even though the R1 margin of the liver is now recognized as less than 1 mm, there are conflicting reports on whether the R1 margin is an independent risk factor for CRLM.…”
Section: Introductionmentioning
confidence: 99%
“…The role of preoperative chemotherapy on resection margin status has been also investigated. Solaini et al conducted a retrospective analysis, but with a propensity score matched analysis, and reported that preoperative chemotherapy was significantly associated with the rate of positive resection margin (25.5% vs. 8.5%) [ 10 ]. Aligned in the same direction, a multicenter study by Benedetti et al analyzed a cohort of 3387 patients who underwent open or laparoscopic liver resection for CRLM in nine European high-volume referral centers.…”
Section: Risk Factors For R1 Resectionmentioning
confidence: 99%
“…Полное удаление метастазов является наиболее эффективным путем лечения больных колоректальным раком с поражением печени, при котором потенциально возможно радикальное излечение [3][4][5]. Статус края резекции при метастазах колоректального рака в печени (МКРП) признан прогностическим фактором, и целью хирургического лечения является достижение негативного края [6]. Ранее признанное расстояние в 10 мм [7,8] с течением времени уменьшали [9,10].…”
Section: отступ от края опухолиunclassified